DIALEKTIKA PEMIKIRAN ULAMA MAZHAB TENTANG WAKAF - Dzulkifli Noor (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
The dialectics of scholars’ thought within the four madhhabs in formulating wakaf (endowment) law illustrate the intellectual dynamics from classical to contemporary Islam. Differences in istinbat (legal derivation) methods among the Hanafi, Maliki, Shafi‘i, and Hanbali schools produce diverse interpretations regarding the definition, pillars, and implementation of wakaf. This study, using a normative legal and qualitative-descriptive approach through literature review, explores these variations and their epistemological implications for modern practice. Findings show that the Hanafi school emphasizes rational reasoning and istihsan (juridical preference), the Shafi‘i school upholds strict adherence to nash and ijma’ (consensus), the Maliki school prioritizes maslahah (public interest) for social adaptability, and the Hanbali school synthesizes textual literalism with pragmatic application. These dialectical differences reflect complementary perspectives that enrich and advance the theoretical and practical development of wakaf law in Islam.